Postures Toward Postcolonial Peace: Repentance, Forgiveness, and Lament1. (October 2022) - Tizon, Al
Each party in any given conflict has a role to play in the process of reconciliation. However, these respective roles are different depending on the power differential within the conflict. The role of the gospel peacemaker is to be aware of the power differential and to call each party to do their part toward reconciliation with one another. For those who have abused their power for self-gain at the expense of others need to repent. For those who have been victimized by this power abuse need to forgive. And both abuser and abused need to lament.